Community Structure and Biodiversity of Soil Ciliates at Dongzhaigang Mangrove Forest in Hainan Island, China - Jing Li; Qingyu Liao; Mei Li; Jinhong Zhang; Nora Fungyee Tam; Runlin Xu (Applied and Environmental Soil Science)
The distribution of soil ciliates in three different habitats within a typical mangrove forest in Dongzhaigang, Hainan, China was investigated. The abundance, biodiversity, and community similarity of ciliates in fresh and air-dried soil with different, physical/chemical properties were analyzed. Three Classes, 11 Orders, 34 Genera, and 70 species of ciliates were found with the first dominant group being Hypotrichida. Ciliate biodiversities followed Site B < Site A < Site C in both fresh and dried samples. Ciliate abundance was positively correlated with soil moisture, salinity, organic matter (OM), total nitrogen (TN), total phosphorus (TP), and sulfate (SO42−), but negatively with pH and total potassium (TK). Site A and Site B and Site B and Site C showed the highest similarity in fresh and dried samples, respectively. The ubiquitous characteristics of ciliate distribution suggested their important role in food webs and nutrient cycling. The presence of Colpodida was linked with mangrove plants.